The Relationship between Insulin Resistance and Type II Ketosis in Dairy Cows - Cuiyu, Zhang; Chang, Zhao; Jiang, Zhang; Cheng, Xia; Hong You, Zhang (Acta Scientiae Veterinariae, 2019)
Background: Cows in perinatal period are prone to ketosis, characterized by increased ketone bodies and decreased blood sugar. Study found that cows with type II ketosis had higher blood glucose levels. This type of ketosis exhibits insulin resistance and impaired glucose tolerance that are similar to type 2 diabetes. The purpose of this study was to investigate the role of insulin resistance(IR) in type II ketosis in dairy cows. Materials, Methods & Results: In one intensive cattle farm, eight cows with ketosis and eight healthy cows that were 14-21 days postpartum were selected. The plasma of experimental dairy cows was collected and tested for the concentration of glucose concentration. Glucose tolerance of blood glucose levels in 120 min was used as the cut-off point to divide the dairy cows into three groups: the abnormal glucose tolerance ketosis group (TH), the normal glucose tolerance ketosis (TL), and the healthy control group. Simultaneously, the indexes of plasma liver function, oxidative stress, and insulin resistance were detected. The results showed that after intravenous glucose injection, there was no significant difference in blood glucose concentration between the TL and control group, while the blood glucose levels in the TH group were always higher than in the other two groups. The insulin sensitivity index (RQUICKI) value was significantly lower in the TH group than in the other two groups. Liver function abnormalities in the TH group were more severe than in the TL and control group. Oxidative stress was higher in the TH group than in the TL and control groups. Discussion: Postpartum dairy cows, with high lactation, consume large amounts of sugar, resulting in a lower blood sugar, and the postnatal dry matter intake peak is later than the peak lactation, which further decreases blood sugar and leads to a negative energy balance in cows. Such ketosis is associated with NEB caused by hypoglycemia, However, a survey of blood glucose concentration in cows with ketosis shows that ketosis can still occur in cows with high blood sugar levels. The pathogenesis of hyperglycemic ketosis is still unclear. Insulin Resistance (IR) refers to tissue sensitivity to insulin decreases, compensatory Islet beta cells secreting insulin thus producing hyperinsulinemia. AST is a typical indicator of liver damage, plasma AST levels in Group TH were significantly higher than the other two groups.The RQUICKI is a key indicator determining whether the body has developed insulin resistance. the plasma insulin sensitivity index of group TH was significantly lower than Group TL and C. BHBA levels in serum is the gold standard for the diagnosis of cow ketosis.The concentration of NEFA and BHBA in the blood is a sign of negative energy balance. The concentration of BHBA and NEFA in the TH group was significantly higher than in the group C, and the concentration of BHBA was higher than the critical value of ketosis. SOD is a metal antioxidant enzyme and its level are key indicators in measuring the removal of oxidizing substances. T-AOC is a measuring indicator for total antioxidant function. The reduction of SOD and T-AOC concentrations in the TH group indicated that the antioxidant capacity of ketone cows with abnormal glucose tolerance was reduced. The above results show that the TH group is severely impaired in liver function, and has a disorder of glucose metabolism, abnormal glucose tolerance and hyperinsulinemi, which also have severe IR. Moreover, the antioxidant capacity of the TH cows with ketosis declined, the body was in a state of oxidative stress. Thus, the occurrence of ketosis in some cows is related to a glucose utilization disorder caused by insulin resistance, and abnormal liver function and oxidative stress are the causes of insulin resistance.